Republic of Equatorial Guinea : 2008 Article IV Consultation; Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for the Republic of Equatorial Guinea. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
Economic growth in Equatorial Guinea recovered sharply in 2007. The opening of a new oil field in late 2006 and a liquefied natural gas facility in mid-2007, supported by increased public infrastructure spending, lifted 2007 economic growth to an estimated 21.4 percent. Executive Directors have welcomed Equatorial Guinea's recent robust economic performance and sound macroeconomic policies that have strengthened fiscal sustainability. Directors have also welcomed the National Development Plan, which provides an appropriate framework for economic and institutional reforms to diversify the economy and enhance external competitiveness.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet